Interprofessional Education and Research in the Health Professions: A Systematic Review and Supplementary Topic Modeling - Cristian Lieneck; Tiankai Wang; David Gibbs; Chris Russian; Zo Ramamonjiarivelo; Arzu Ari (MDPI AG, 2022)
Interprofessional education (IPE) has grown in popularity over the years because it is effective in training future health professionals and serves as the engine of productivity in healthcare-related research. The research team, consisting of higher education faculty in various health profession disciplines, conducted a systematic review of existent IPE literature targeting both graduate and under-graduate students. The main purpose of the systematic review was to categorize research and analyze IPE studies to determine sub-constructs that entail both barriers and facilitators often related to occurrences in primary provider, learner, and researcher IPE initiatives. If identified, IPE training and related curriculum plans were also analyzed in this review. The research team wanted to identify any/all potential instances of the use of research activities in coordination with IPE training to identify underlying constructs to support future college and program-specific andragogy initiatives. Review results demonstrate three categorical constructs related to IPE initiatives in higher education health professions programs (provider, learner, and researcher stakeholder perspectives). Results further demonstrate provider IPE challenges surrounding limited resources and a willingness to participate, while both patient experience and teamwork foci were identified as common IPE session themes. Further, the learners' perspectives included a challenge related to a willingness to participate, as well as the patient experience focus. Review constructs were further validated using supplementary topic modeling. To the best of our knowledge, this is the first study that combined systematic review with a supplementary topic modeling. Findings support ongoing pedagogy and research efforts related to IPE activities for health professions programs in higher education.